Dynamic geometries. Te Wero bridge as a pacific monument - Young, E; Davis, M; Douglas, C; Ceelen, V; Stevens, B; Phuong, DK; Jones, W; Fordham, F; Xu, C; Chou, W; Neville, H (AUT University, 2007)
Te Wero bridge re-interprets traditional notions of monumentality by projecting itself as a dynamic point of exchange. The bridge is a new kind of icon for Auckland. Positioned to articulate a subtle adjustment on the Quay St / Jellicoe St axis, it plays its part in a series of urban callings. It offers the challenge of arrival and departure, and sets up a continual dialogue between the city and Wynyard Quarter. Gently wavering masts respond to environmental shifts. On opening, the structure becomes taut, and the roadway rises to scribe an anthropomorphic arc. On closing, the bridge lowers itself back into place, gesturing a precise offering, and providing the necessary tolerance. The event is a study of poise and elegance. The bridge is structurally efficient, with its tensegrity tower, geometrically folded decks, and a gravity and spring-assisted cable and winch system. Te Wero bridge acts as a symbol of the First City of the Pacific not only by its physical presence, but through its articulation of what it means to be Pacific.